2020
DOI: 10.1007/s43152-020-00001-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Haematopoiesis

Abstract: Purpose of Review This review examines the influences of active vitamin D on 'developmental' haematopoiesis and the immune cells produced. Haematopoiesis gives rise to the platelets, erythrocytes and a wide range of immune cell types each of which performs a specific role to protect the organism from a myriad of infectious agents. The newly produced immune cells, for example, monocytes, dendritic cells and T and B lymphocytes, are activated in response to the presence of an infectious agent and differentiate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The vitamin D receptor (VDR) ، which is expressed by immune cells، is involved in the control of innate and adaptive immunity ، study conducted in vitro and in vivo have shown that calcitriol decreases cytokine production Interleukin-10 (IL-10) is released lymphocytically when VDR is activated ، and this increases the production of inflammatory cytokines in stromal and accessory cells (18) ، while also having anti-inflammatory and proliferative effects on erythroid progenitors. Another theory is that calcitriol directly activates erythroid progenitors because vitamin D has been shown to have an impact on bone marrow function (19) . Additionally ، the active form of vitamin D ، 1 ، 25 hydroxyvitamin D (1-25(OH)2D) ، is present in bone marrow at levels that are hundreds of times higher than in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D receptor (VDR) ، which is expressed by immune cells، is involved in the control of innate and adaptive immunity ، study conducted in vitro and in vivo have shown that calcitriol decreases cytokine production Interleukin-10 (IL-10) is released lymphocytically when VDR is activated ، and this increases the production of inflammatory cytokines in stromal and accessory cells (18) ، while also having anti-inflammatory and proliferative effects on erythroid progenitors. Another theory is that calcitriol directly activates erythroid progenitors because vitamin D has been shown to have an impact on bone marrow function (19) . Additionally ، the active form of vitamin D ، 1 ، 25 hydroxyvitamin D (1-25(OH)2D) ، is present in bone marrow at levels that are hundreds of times higher than in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Findings regarding the regulation of gene expression have revealed that there are links between the actions of VD and cytokines. These include influences on the production/action of the hematopoietic cytokines that are essential to the development and function of the blood cells (5).…”
Section: Introductionmentioning
confidence: 99%